If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(3z + -4) = 0 Reorder the terms: -1(-4 + 3z) = 0 (-4 * -1 + 3z * -1) = 0 (4 + -3z) = 0 Solving 4 + -3z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3z = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3z = 0 + -4 -3z = 0 + -4 Combine like terms: 0 + -4 = -4 -3z = -4 Divide each side by '-3'. z = 1.333333333 Simplifying z = 1.333333333
| 3-2=2-5 | | 3y+5+2y-7=153 | | 3x+1=1x+13 | | 8x^2-12x-4=0 | | 5x^2=210x | | g-2y=9 | | y-12=-2x-2 | | -2y+x=9 | | 7-5x=-8(6+2x) | | -3x+10x= | | 3(4-2x)=-2(4x-1) | | -6(-2-2g)= | | 5x+2X-3= | | 4x+y^2=12 | | 2a+4-8a-19= | | -18-6= | | 2(6m+8)= | | 6(10+10g)+2= | | z+(-7)=-5 | | 2ln(x+1)=ln(1-2x) | | .42-1.2=.3r+.6 | | X+11=3x+31 | | 2h=d | | 2(1+8a)+8a= | | 3x-35=125 | | w+6=-9 | | 9m-3m(m+6)=2(m+1) | | -5(-2t+-8)= | | 2.5x-5+8=19.5 | | 0.5n-6=12 | | -1.5x+y=1 | | -1.5+y=1 |